2000
DOI: 10.1007/s002280050714
|View full text |Cite
|
Sign up to set email alerts
|

QT-interval prolongation by non-cardiac drugs: lessons to be learned from recent experience

Abstract: This has fostered discussion on the molecular mechanisms underlying the class-III antiarrhythmic effect shared by apparently disparate classes of drugs, on the clinical relevance of this side effect and on possible guidelines to be followed by drug companies, ethics committees and regulatory agencies in the risk-benefit assessment of new and licensed drugs. This review provides an update on the different classes of non-cardiac drugs reported to prolong the QT interval (e.g. histamine H1-receptor antagonists, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
113
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(116 citation statements)
references
References 137 publications
2
113
0
1
Order By: Relevance
“…The risk increases when 2 or more such medications are administered concurrently. [60][61][62] Among the patients in our study who had aLQTS, 10 (22%) received 2 or more QTc-prolonging medications. Among the patients who did not have aLQTS, 4 (10%) received more than 1 QTc-prolonging medication.…”
Section: Medications and Alqtsmentioning
confidence: 92%
“…The risk increases when 2 or more such medications are administered concurrently. [60][61][62] Among the patients in our study who had aLQTS, 10 (22%) received 2 or more QTc-prolonging medications. Among the patients who did not have aLQTS, 4 (10%) received more than 1 QTc-prolonging medication.…”
Section: Medications and Alqtsmentioning
confidence: 92%
“…Concerns have been raised recently regarding its arrhythmogenic potential, a risk already known to be associated with the first marketed macrolide, erythromycin. [1][2][3][4][5][6] Several case reports have described QTinterval prolongation, 7-9 torsades de pointes [10][11][12] and polymorphic ventricular tachycardia 13 following use of azithromycin. Many observational studies have reported conflicting results about the association between azithromycin use and cardiovascular death.…”
mentioning
confidence: 99%
“…Drug-induced (acquired) long QT syndrome, an effect manifested as prolongation of the QT interval on the surface electrocardiogram (ECG), has drawn increasing attention from regulatory agencies and the pharmaceutical industry in recent years (De Ponti et al, 2000Fermini and Fossa, 2003). The presence of delayed repolarization favors the genesis of "early after-depolarization" (EAD), which can initiate an arrhythmia referred to as "triggered activity" (Zabel et al, 1997).…”
mentioning
confidence: 99%